Fatal Stevens-Johnson syndrome induced by phenytoin: a case report - Budania, Ritu J.; Dakhale, Ganesh N.; Sontakke, Smita D.; Patnaik, Pavitra S. (International Journal of Basic & Clinical Pharmacology, 2017)
Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are rare (one to two per 10,00,00 population per year) but life threatening adverse drug reactions. Drugs commonly implicated are anti-epileptics, anti-microbials and non-steroidal anti-inflammatory drugs (NSAIDS). Amongst anti-epileptics, carbamazepine and phenytoin are the major culprits. We report here a fatal case of SJS due to phenytoin.